Attention as a Valuable Resource. (3rd July 2017) - Stroud, Natalie Jomini
Abstract : Keeping up with the news and monitoring public affairs are typically considered civic obligations. Yet there is a great deal of competition for people's limited attention. Some studies explore when people tune in to the news and what sorts of public affairs content attract our time, but these topics warrant more research. Scholars concerned with the news media's political role must better understand what leads people to the news in the first place. The practical import of this work is pronounced in an era where news organizations struggle to make ends meet. The purpose of this essay is to categorize what we know about what motivates people to tune in to news and then to propose a research agenda for analyzing attention to public affairs content.